Investigation of ZnO nanrod solar cells with layer-by-layer deposited CdTe quantum dot absorbers - Briscoe, Joe (Cranfield University, 2011)
Innovation in solar cell design is required to reduce cost and compete with traditional power generation. Current innovative solar technologies include nanostructured dye-sensitised solar cells and polymer solar cells, which both contain organic materials with limited lifetime. This project aims to combine the advantages of ZnO nanorods and quantum dot (QD) absorbers in an all-inorganic solar cell, using the layer-by-layer (LbL) process to increase light absorption in the cell. Cont/d.